Raising the Dead - Holland, Sharon Patricia,Pease, Donald E. (Duke University Press, 2000)
Raising the Dead is a groundbreaking, interdisciplinary exploration of death's relation to subjectivity in twentieth-century American literature and culture. Sharon Patricia Holland contends that black subjectivity in particular is connected intimately to death. For Holland, travelling through
10.1515/9780822380382